2022
DOI: 10.3390/cancers14153690
|View full text |Cite
|
Sign up to set email alerts
|

Blood Immune Cell Biomarkers in Lung Cancer Patients Undergoing Treatment with a Combination of Chemotherapy and Immune Checkpoint Blockade

Abstract: Although immune checkpoint inhibitor (ICI) therapies have improved the treatment of patients with advanced non-small cell lung cancer (NSCLC), several patients do not achieve durable clinical responses. Biomarkers for the prediction of therapy responses are urgently needed. To identify blood cell parameters correlating with patients’ survival, immune cells from 90 patients with NSCLC undergoing a combination of ICI and chemotherapy were prospectively monitored. At the time point of the first and third antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…If the disease progressed early, before the expected time point 2, a sample of peripheral blood was collected when assessing the disease progression by CT. Complete blood counts, including absolute monocyte count (AMC), absolute neutrophil count (ANC), absolute lymphocyte count (ALC), and platelet count, were recorded at the baseline (time point 1) and at the third cycle of combined therapy (time point 2) ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…If the disease progressed early, before the expected time point 2, a sample of peripheral blood was collected when assessing the disease progression by CT. Complete blood counts, including absolute monocyte count (AMC), absolute neutrophil count (ANC), absolute lymphocyte count (ALC), and platelet count, were recorded at the baseline (time point 1) and at the third cycle of combined therapy (time point 2) ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…All patients gave written informed consent for the study's proposal and procedures. In a former study, 90 patients with histologically confirmed unresectable locally advanced or metastatic lung cancer, prior to PD-1 or PD-L1 blockade treatment in combination with chemotherapy, were prospectively enrolled from June 2019 to June 2021 (Table 1 in [11]). In total, 12 of the 36 patients surviving ≥ 12 months consented to a third blood draw and were included in the current pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples, antibody staining, and flow cytometry. Blood samples of a former study [11] were collected before the initiation of immune/chemotherapy (time point 0, baseline) and prior to the third therapy cycle (t 1 ). For the current pilot study, 12 patients with an OS of at least 12 months consented to a third blood draw (t 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from reporting NLR and PLR, other blood cell counts included derived neutrophil-lymphocyte ratio (dNLR), absolute lymphocyte count (ALC), absolute neutrophil count (ANC), absolute platelet count (APC), absolute eosinophil count (AEC), and leukocyte count and its differentials. Receiver operating characteristic (ROC) curves were used in nine studies (25,33,36,(38)(39)(40)(41)(42)(43) to determine the optimal cutoff value for NLR and PLR.…”
Section: Research Characteristicsmentioning
confidence: 99%